The Effect of Nepotism on The Agency Cost in The Family Business - Kumral, Tuğçe (My University, 2019)
The aim of this study is to examine the effect of nepotism on the agency cost in the family businesses. In the literature, studies on the negative aspects of nepotism have been given emphasize. The aim of the study was determined that nepotism might have positive aspects in some cases and that it could eliminate the problems like agency costs. The population of the research is composed of the managers of the family businesses in Istanbul. An invitation e-mail was sent to 25 of the family businesses in different sectors in order to ensure their participation in the research. The managers of 4 family businesses who volunteered to participate in the study comprise the sample of the study. When the literature is examined, it has been observed that similar studies conducted previously on this subject have been carried out by quantitative methods. Therefore, qualitative research method will be used. After that, descriptive analysis technique will be used to analyze the data.